Assessment of patients’ satisfaction and associated factors among outpatients received mental health services at public hospitals of Mekelle Town, northern Ethiopia - Haftom Desta; Tesfay Berhe; Solomon Hintsa (International Journal of Mental Health Systems, 2018)
Abstract Background Satisfaction is the psychological state that results from confirmation or disconfirmation of expectations with reality. Patients’ satisfaction is a healthcare recipient’s reaction to salient aspect of the contexts, process and result of their service experience. The aim of this study was to assess patient satisfaction and associated factors among outpatients receiving mental health services at public hospitals in Mekelle town. Objectives To assess patient satisfaction and associated factors among outpatients receiving mental health services at public hospitals in Mekelle town, northern Ethiopia. Methods An institution based cross-sectional study was conducted among 415 outpatients receiving mental health services at public hospitals in Mekelle town from September 2013 to August 2014. The data were collected using standardized, structured pre-tested questionnaire. Participants were selected by systematic random sampling technique. Satisfaction rate was examined with the client satisfaction questionnaire (CSQ-8), having four responses ranging from poor to very good. Descriptive summary using percentages, frequency and graph were used to present study results. Multivariate logistic regressions with 95% confidence interval (CI) were used to assess the strength and p-value < 0.05 was used to indicate the significance of the association. Results A total of 415 respondents were enrolled, with a response rate of 100% and magnitude of satisfaction of 72%. The predictors associated with patient satisfaction were higher education (AOR = 0.34; 95% CI 0.24, 0.97), longer waiting time (AOR = 0.01; 95% CI 0.002, 0.07), having a diagnosis of psychosis (AOR = 2.36; 95% CI 1.41, 5.72) were significantly associated with satisfaction. Conclusion and recommendation More than one-four of patients receiving mental health services were dissatisfied with the service they received. Improvement in accessibility and availability of drugs, minimizing consultation time (< 45 min) or increasing number of OPD units are important to improve satisfaction.